Fiber formation and properties of polyester/lignin blends. Issue 46 (13th July 2019) - Pospiech, Doris; Korwitz, Andreas; Eckstein, Kathrin; Komber, Hartmut; Jehnichen, Dieter; Suckow, Marcus; Lederer, Albena; Arnhold, Kerstin; Göbel, Michael; Bremer, Martina; Hoffmann, Anton; Fischer, Steffen; et al.
ABSTRACT: Thermotropic liquid crystalline polyesters with varied chemical structure are synthesized by melt transesterification polycondensation. They are employed as matrix for blends with lignin materials to obtain melt‐spinnable precursors for carbon fibers. The lignin samples are carefully purified by fractionation, enzymatic removal of reducing sugars, and subsequent modification of the terminal OH groups. Effective melt blending is achieved with liquid‐crystalline aromatic–aliphatic polyesters having melting ranges that match the softening temperature of the lignin fractions, which is necessary to prevent thermal decomposition of the lignin. Polyester/lignin blends are partially compatibilized, phase‐separated materials. The polyester/lignin materials are melt‐spun successfully. The fiber properties depend on the lignin purification process. X‐ray scattering reveals that orientation in lignin‐containing fibers is maintained. First experiments show that the fibers can be converted successfully to carbon fibers by thermal annealing procedures. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 48257. Abstract : Thermotropic liquid crystalline polyesters (LCP) are explored as polymer matrix for lignin to achieve fiber spinning. The lignin types used are carefully fractionated, chemically modified and melt mixed with the LCP synthesized. The blends are partially miscible and are melt spun into fibers as potential new precursors for carbon fibers.